Steal: Instinct #3 - Patterson, James; Roughan, Howard (New York Grand Central, 2022)
Imagine everyone's surprise when Carter von Oehson, a sophomore in Dr. Dylan Reinhart's Abnormal Psychology class, posts on Instagram that he plans to kill himself. Twenty-four hours later and still no one has seen him ... The one person convinced he's still alive is his father, Mathias von Oehson, founder and CEO of the world's largest hedge fund. But what Mathias knows and how he knows it would ultimately reveal a secret so damaging that it would be as if he were committing suicide himself ... Dylan now finds himself wrapped up in multi-million-dollar secrets and danger. It's going to take every bit of his expertise, and the brilliant and headstrong NYPD detective Elizabeth Needham, to stay ahead of both his enemy ... and his employer.
Keywords: College teachers; Missing persons; Art thefts; Rich people; Secrecy; Investigations; Fathers and sons; .Thriller.; New York (State); Detective and mystery fiction